Copyright interpreting the law for libraries, archives and information services - Cornish, Graham P. (Facet Publishing, 2019)
Cornish's 'Copyright' is the standard work in its field and is indispensable for all librarians and information professionals who are looking for solutions to their copyright problems. The book explains the provisions of the UK Copyright Act and supporting legislation in quick and easy question-and-answer form. This revised edition is fully updated to take into account all of the changes that have come into force since the 6th edition was published in 2015.